2016
DOI: 10.1038/srep31023
|View full text |Cite
|
Sign up to set email alerts
|

The Airway Microbiome at Birth

Abstract: Alterations of pulmonary microbiome have been recognized in multiple respiratory disorders. It is critically important to ascertain if an airway microbiome exists at birth and if so, whether it is associated with subsequent lung disease. We found an established diverse and similar airway microbiome at birth in both preterm and term infants, which was more diverse and different from that of older preterm infants with established chronic lung disease (bronchopulmonary dysplasia). Consistent temporal dysbiotic ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
181
2
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(193 citation statements)
references
References 43 publications
(48 reference statements)
6
181
2
4
Order By: Relevance
“…Contrary to the traditional belief that the human neonatal respiratory tract is sterile at birth, current studies indicate that the human respiratory tract microbial colonization begins in utero 100,101 or shortly after birth 102,103 . A recent study demonstrated that the lung microbiome, including the relative abundance of bacterial phyla and diversity index of the preterm and term neonates were similar at birth irrespective of the gestational age and the mode of delivery.…”
Section: Pathogenesiscontrasting
confidence: 90%
See 1 more Smart Citation
“…Contrary to the traditional belief that the human neonatal respiratory tract is sterile at birth, current studies indicate that the human respiratory tract microbial colonization begins in utero 100,101 or shortly after birth 102,103 . A recent study demonstrated that the lung microbiome, including the relative abundance of bacterial phyla and diversity index of the preterm and term neonates were similar at birth irrespective of the gestational age and the mode of delivery.…”
Section: Pathogenesiscontrasting
confidence: 90%
“…A recent study demonstrated that the lung microbiome, including the relative abundance of bacterial phyla and diversity index of the preterm and term neonates were similar at birth irrespective of the gestational age and the mode of delivery. Firmicutes and Proteobacteria were the predominant microbes at birth 103 . Factors such as chorioamnionitis, antibiotic exposure, mode of delivery, method of feeding, and bowel colonization can decrease bacterial diversity and increase pathogenic microbial colonization in the lungs 104 , which may potentially lead to an inflammatory lung phenotype that ultimately contributes to the development of BPD.…”
Section: Pathogenesismentioning
confidence: 98%
“…2930 The abnormal immune responses and enhanced inflammatory responses of prematurity generate a unique host environment, which, in combination with early nosocomial exposures, results in distinct microbial communities colonizing different systems. 31 32 An example is the increasingly clear link between the abnormal gut microbiota composition in PM infants and the development of necrotizing enterocolitis. 32 In addition, abnormalities in the airway microbiome diversity of PM infants have also been described in association with the development of bronchopulmonary dysplasia (BPD), 31 the most common chronic respiratory complication in this vulnerable population.…”
Section: Discussionmentioning
confidence: 99%
“…At the phylum level, PM infants showed increased Proteobacteria (major group of Gram-negative bacteria) and decreased Firmicute (Gram-positive bacteria such as Clostridium and Lactobacillus ), which is an airway microbiome signature recently described in PM newborns, particularly in those with increased BPD risk. 31 …”
Section: Discussionmentioning
confidence: 99%
“…There is increasing interest in the possible role of lung microbiome in the risk for BPD with several studies showing that multiple antenatal and postnatal factors, such as antibiotic use, nutrition, and sepsis can alter the normal development of lung microbiome [25, 26]. The potential role of lung dysbiosis in the development of BPD needs to be further elucidated.…”
Section: Changes In the Pathogenesis Of Bpdmentioning
confidence: 99%